2008
DOI: 10.1007/s10812-008-9044-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carbon in soil by laser spectral analysis

Abstract: We have used a combination laser/electrospark method for fast determination of carbon content in soil. Excitation of the spectra is carried out both directly in a laser ablation plume and when a pulsed electric discharge is applied to it. We have plotted a calibration curve that is linear for the major concentration range of practical importance for the analyte element, all the way up to 8.6%. The carbon detection limit for the combination discharge approach is 0.07%. We have analyzed the ratio of the nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…For example, Cremers et al (2001) and Ebinger et al (2003) calibrated LIBS to samples from three farm fields in Colorado, and Martin et al (2010) calibrated LIBS using soil samples from Illinois, Michigan, and North Dakota farm fields. Furthermore, the range in measured TC and IC content (55 and 45 gC kg -1 , respectively) was similar to soil carbon content ranges reported by others [32 to 57 gC kg -1 , (Bel'kov et al, 2008;Belkov et al, 2009;Cremers et al, 2001;Ebinger et al, 2003;Martin et al, 2003;Martin et al, 2010;Martin et al, 2007)]. Researchers therefore suspect that difficulties associated with interrogation of intact cores contributed to relatively low calibration and validation statistics.…”
Section: Discussionsupporting
confidence: 82%
“…For example, Cremers et al (2001) and Ebinger et al (2003) calibrated LIBS to samples from three farm fields in Colorado, and Martin et al (2010) calibrated LIBS using soil samples from Illinois, Michigan, and North Dakota farm fields. Furthermore, the range in measured TC and IC content (55 and 45 gC kg -1 , respectively) was similar to soil carbon content ranges reported by others [32 to 57 gC kg -1 , (Bel'kov et al, 2008;Belkov et al, 2009;Cremers et al, 2001;Ebinger et al, 2003;Martin et al, 2003;Martin et al, 2010;Martin et al, 2007)]. Researchers therefore suspect that difficulties associated with interrogation of intact cores contributed to relatively low calibration and validation statistics.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, as reported by Cremers and Chinni in their recent review: 33 “It is not an exaggeration to state that LIBS is probably the most versatile method of elemental analysis that is currently practiced.” In this review, several examples are given. Our selection includes topics relevant to the environment (soils and vegetation 627,,–649 and minerals 650,,–655 ), aerosols and bioaerosols, 656,,–670 combustion, 671,,–682 forensics, 683,,–691 pharmaceutical, 692,,–697 medical, 698,…”
Section: Review Outlinementioning
confidence: 99%
“…The current one-sample-out calibrations also approach accuracies reported for determining C in processed soil samples. 4,6,45,46 Although LIBS has been proposed as an in situ soil C measurement tool, 2 it remains to be demonstrated that the in situ results will quantitatively and statistically match those obtained with prepared samples. It is common practice for soil samples to be processed using some combination of air drying, sieving (2 mm mesh), packing in quartz tubes, pelletizing under pressure, or treating with acid to remove carbonates prior to LIBS analysis for TC or SOC.…”
Section: Resultsmentioning
confidence: 99%